WA-DILA (WHATSAPP-BASED INTELLIGENT ASSISTANT): CHATBOT UNTUK MENINGKATKAN LAYANAN INFORMASI DI LEMBAGA SERTIFIKASI PROFESI - Dani Anggoro; Yasmika Baihaqi; Aulia Tasya Putri. Dh; Nur Rahma Danitta; Muhammad Hidayah Alfino (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
The utilization of information technology has transformed the delivery of public services, including competency certification information services provided by Professional Certification Institutions (LSP). WhatsApp, as one of the most popular instant messaging applications in Indonesia, is commonly used as a primary communication platform. However, the manual information delivery process at LSP Universitas Muhammadiyah Metro has led to several issues, such as delayed responses, overlooked messages, and inconsistent information. This study developed an Artificial Intelligence (AI)-based chatbot integrated with Natural Language Processing (NLP) on the WhatsApp platform, named WA-DILA (WhatsApp-based Intelligent Assistant). The system was developed using the Waterfall model, encompassing stages of requirements analysis, system design, implementation, testing, and maintenance. Node.js and MySQL were utilized in the development, and system functionality was evaluated using black box testing. WA-DILA was successfully implemented and capable of automatically responding to various user inquiries. All features functioned as expected based on testing results. Out of 217 users, 206 provided feedback, with 88% giving positive ratings (scores 4 and 5), indicating a high level of satisfaction with the chatbot service. WA-DILA effectively enhanced the efficiency and quality of information services at the LSP through fast, automated, and consistent responses. This solution demonstrates strong potential for broader implementation in other digital information service contexts, supporting the transformation of public services through the adoption of intelligent technology-based systems.